The Emerging Role of Artificial Intelligence in Healthcare - Rathore, Farooq Azam; Rathore, Muhammad Ahmad (Journal of the Pakistan Medical Association, 2023)
Artificial intelligence (AI) is increasingly being used in the field of healthcare to improve the efficiency and accuracy of medical diagnoses, treatment plans, and decisionmaking.1 It has the potential to transform the way healthcare is delivered and improve patient outcomes. There are many examples of the use of artificial intelligence (AI) in healthcare. One way that AI is being used in healthcare is by developing machine learning algorithms that can analyze vast amounts of patient data and identify patterns and trends that may not be immediately apparent to humans.2 This can be particularly useful in identifying early signs of diseases or conditions, allowing for earlier diagnosis, treatment, prognosis evaluation, and more. Another application of AI in healthcare is through the use of natural language processing (NLP). NLP systems can analyze electronic medical records (EMR) and extract important information, allowing healthcare providers to access and interpret patient data conveniently.3 This can help healthcare providers access and interpret patient data more easily, leading to more informed decision-making and better patient care. AI can also be used to assist with tasks such as image analysis, allowing for more accurate analysis and efficient diagnosis of medical images such as CT scans or X-rays.4 In addition, AI can be used to help automate routine tasks, freeing up healthcare providers to focus on more complex and higher-level tasks that require human expertise.5 Machine learning algorithms can analyze large amounts of patient data and identify patterns and trends that may not be immediately apparent to humans.6 This can be useful in identifying early signs of diseases or conditions, leading to earlier diagnosis and treatment. AI-powered chatbots or virtual assistants can help with tasks such as appointment scheduling and medication reminders.7 Systems that can assist with the automation of routine tasks, freeing up healthcare providers to focus on more complex and higher-level tasks that require human expertise. Predictive analytics systems can forecast patient outcomes and help healthcare providers make informed decisions about treatment plans.8 Personalized medicine systems can help tailor treatment plans to individual patients based on their specific needs and characteristics. These are just a few examples of the many ways in which AI is being used in healthcare. It is important to note that AI in healthcare is still in its early stages, and the potential applications of the technology are likely to expand significantly in the coming years.